Dampak Pandemi Covid-19 terhadap Kinerja Universitas Advent Indonesia (UNAI) - Albinur Limbong (TeIKa, 2021)
Covid-19 pandemic has hit Indonesia or even the world since early 2020 Indonesia, and many people have suffered from the disease due to the pandemic and even some of them have died. Besides killing so many people, Covid-19 pandemic has been a night mare for many people living in this world, it has been destroying our economics, or even every aspect of our life, including education. Indonesian government has applied a lock down regulation, where people must work from home. No exception, UNAI has to change from offline teaching to become online teaching, although UNAI is a dormitory school. Due to the sudden change in teaching and learning processes, there should be an impact to student achievement, faculty performance or even UNAI as an institution. It is interesting to see whether the covid-19 pandemic brings negative effects or are there any positive effects. The purpose of this study is to see whether covid-19 pandemic influence student, teacher or even UNAI’s performance. The performance of student is seen by the GPA (Grade Point Average), while the teacher performance is seen by teacher evaluation and the performance in research and publications. The parameters of UNAI performance involve students and teachers’ performance, besides other institutional indicator, such as financial, ranking and accreditation, etc. The study was carried out since March 2020 until June 2021. The results of the study show that the covid-19 pandemic brought a positive impact in the academic achievement of UNAI students, since there was a significant increase in GPA from 3.21 to 3.26. However, in terms of student evaluation on teacher performance there was a slight decrease 4.413 to 4.386, although the decrease was not significant. The percentage of teacher published in a recognized journal and book publication increased from around 40% (before pandemic) to 55% (during pandemic). Institutionally, UNAI performed even better during pandemic, in terms of webometrics world ranking, accreditation, and financial indicators (working capital, liquidity and cash). In conclusion, regardless its negative sides, the covid-19 pandemic has brought a positive impact to UNAI. Covid-19 pandemic is like a blessing in disguise to UNAI.